Magnesium-based absorbable alloy

By adding a small amount of lithium, zinc, calcium and manganese to the magnesium-based alloy, and performing cold processing and annealing treatment, the problems of insufficient strength, ductility and biocompatibility in medical device applications have been solved, and a high ductility and high strength magnesium-based alloy is achieved, which is suitable for medical devices that require significant plastic deformation.

CN113993486BActive Publication Date: 2025-05-02FORT WAYNE METALS RES PROD LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080040830.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-03
Filing Date
2020-06-02
Publication Date
2025-05-02
Estimated Expiration
2040-06-02

AI Technical Summary

Technical Problem

In medical device applications where significant plastic deformation is required, the combination of parameters such as strength, ductility and biocompatibility is not sufficient to meet specific needs.

Method used

Using a magnesium alloy containing a small amount of lithium, zinc, calcium and manganese, with chemical compositions of 1-5% lithium, 0.2-2.0% zinc, 0.1-0.5% calcium and 0.1-0.8% manganese, the strength and ductility of the alloy are improved by cold processing and annealing treatment.

Benefits of technology

Magnesium-based alloys with high ductility and high strength are suitable for medical devices that require significant plastic deformation, and have good in vivo degradation characteristics and biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113993486B_ABST
    Figure CN113993486B_ABST
Patent Text Reader

Abstract

Magnesium alloys contain small amounts of lithium, zinc, calcium and manganese. For example, a magnesium alloy may contain 1-5% by weight lithium, 0.2-2.0% by weight zinc, 0.1-0.5% by weight calcium and 0.1-0.8% by weight manganese. These alloying elements are all nutritional elements, so that the alloy of the present invention can be safely decomposed in the body and then absorbed and / or excreted by the body. Li, Zn, Ca and Mn each contribute to the solid solution strengthening of the alloy. Ca also acts as a grain refiner, while Zn and Ca both form intermetallic compounds that strengthen and control corrosion. Optionally, the alloy may also contain a small amount of yttrium to increase strength and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 856,293, filed on June 3, 2019, entitled MAGNESIUM-BASED ABSORBABLE ALLOYS, the entire disclosure of which is hereby expressly incorporated herein by reference. Background of the Invention 1. Technical Field

[0004] The present invention relates to wires for use in biomedical applications, and in particular, to biodegradable wires for use in medical devices such as stents.

[0005] 2. Description of Related Technology

[0006] Specialized absorbable materials are the focus of ongoing development for surgical implant applications. For example, design efforts to create absorbable stents have focused primarily on balloon dilatation techniques for coronary artery lesions and may include polymeric materials such as poly-L-lactic acid (PLLA) or poly-L-glycolic acid (PLGA), or metallic materials such as magnesium (Mg), iron (Fe), or zinc (Zn)-based alloys. Some research approaches also focus on hybrid materials, including various combinations of absorbable polymers and metals. Although such materials are absorbable, their functional properties, such as mechanical strength and ductility, corrosion rate, or biocompatibility, may not be sufficient for specific applications.

[0007] Other applications of resorbable materials, including nutrient metal resorbable materials, include temporary fracture fixation devices such as bone plates. In some cases, bone plates must provide a specified level of mechanical strength during bone regeneration after fracture, but the presence of the plate after fracture healing may lead to complications and / or require surgical removal.

[0008] Many magnesium-based alloys have been investigated for their utility in this absorbable implant application. For example, WE43 is an alloy that typically contains 4 wt% Y and 3 wt% other rare earths (primarily Nd) and 0.5% Zr. This alloy has relatively high strength, moderate ductility, and generally acceptable corrosion rates. However, it does have relatively large amounts of rare earth elements, which may have a long residence time in the body.

[0009] Other magnesium-based alloys have been investigated that do not contain rare earth elements, but instead contain additions that are inherent to the body, such as Zn, Ca, and / or Mn. These alloys are generally less strong than alloys containing rare earths, but have comparable ductility. Their corrosion rates can be adjusted based on the specific precipitates formed by heat treatment. For some applications, such as wire-based medical devices, these alloys may not have sufficient strength.

[0010] Furthermore, the ductility of the above-mentioned known rare earth and magnesium-based alloys is only moderate, and for some devices (such as staples, clips or stents) that require significant plastic deformation, greater ductility is required. Greater ductility also improves the manufacturability of semi-finished products of such devices.

[0011] It is known that adding lithium (Li) to Mg will increase the ductility of the alloy. When the lithium content is greater than 11 wt%, the crystal structure of the alloy changes from a brittle hexagonal close-packed structure (HCP) to a ductile body-centered cubic structure (BCC). Between about 6 wt% and about 11 wt%, a dual-phase structure HCP and BCC exists, while below 6 wt% Li, the intrinsic HCP is retained. Mg-Li binary alloys, Mg-Li-Ca alloys, and Mg-Li-Al-rare earth alloys have been studied as potential absorbable metals. While lithium has been found to increase ductility, it also reduces strength and may reduce corrosion rates. It is also a psychoactive element and large amounts of lithium in the alloy may have associated adverse effects.

[0012] Known absorbable magnesium-based alloys thus have various combinations of strength, ductility, biocompatibility and corrosion resistance. However, for devices requiring significant plastic deformation, no known absorbable alloy has an optimal combination of these parameters.

[0013] What are needed are improvements over the foregoing. Summary of the invention

[0014] The present invention relates to a magnesium alloy containing a small amount of lithium, zinc, calcium and manganese. For example, the magnesium alloy may contain 1-5% by weight of lithium, 0.2-2.0% by weight of zinc, 0.1-0.5% by weight of calcium and 0.1-0.8% by weight of manganese. These alloying elements are all nutritional elements, so that the alloy can be safely decomposed in the body and then absorbed and / or excreted by the body. Li, Zn, Ca and Mn each contribute to the solid solution strengthening of the alloy. Ca also acts as a grain refiner, while Zn and Ca both form intermetallic compounds that strengthen and control corrosion. Optionally, the alloy may also contain a small amount of yttrium to increase strength and corrosion resistance.

[0015] In one form thereof, the present disclosure provides an alloy for an absorbable medical device comprising 1.0-5.0 wt % lithium, 0.2-2.0 wt % zinc, 0.1-0.5 wt % calcium, 0.1-0.8 wt % manganese, the balance being magnesium and unavoidable impurities.

[0016] BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and other features and objects of the present invention, as well as the manner in which they are achieved, will become more apparent and the present invention itself will be better understood by referring to the following description of the embodiments of the present invention in conjunction with the accompanying drawings, in which:

[0018] Figure 1 is a front view illustrating the geometry of a braided stent having a diameter Ds according to the present disclosure, the stent comprising wire elements formed into a mesh-like tubular stent;

[0019] Figure 1A is a perspective view of another braided stent including wire elements formed into a mesh-like tubular stent according to the present disclosure;

[0020] Figure 2 is a schematic diagram illustrating an exemplary forming process of a monolithic wire using a lubricated draw die;

[0021] Figure 3 is a schematic diagram illustrating an exemplary forming process of a composite wire using a lubricated draw die;

[0022] Figure 4 is an elevation view of a wire according to the present disclosure prior to a final cold working process;

[0023] Figure 5 yes Figure 4 A front view of the line after the final cold working process; and

[0024] Fig. 6A is a stress-strain graph drawn to scale showing a control material juxtaposed with a material made in accordance with the present disclosure;

[0025] Figure 6B is a stress-strain diagram drawn to scale showing additional properties of materials made according to the present disclosure;

[0026] Figure 6C is a graph drawn to scale showing the degradation characteristics of materials made according to the present disclosure relative to various control materials;

[0027] Figure 7 is a perspective view of a medical screw designed for use in vivo and made from a material according to the present disclosure; and

[0028] Figure 8 is a perspective view of a septal occluder designed for in vivo use and incorporating a wire in accordance with the present disclosure.

[0029] Corresponding reference characters indicate corresponding parts throughout the several views. Although the exemplifications set out herein illustrate embodiments of the invention, the embodiments disclosed below are not intended to be exhaustive or to be construed as limiting the scope of the invention to the precise forms disclosed. DETAILED DESCRIPTION OF THE INVENTION

[0031] 1. Introduction

[0032] The alloy of the present disclosure is a magnesium-lithium-zinc-calcium-manganese (Mg-Li-Zn-Ca-Mn) alloy that exhibits an absorbable alloy that exhibits high ductility and machinability, high strength, and a suitable in vivo degradation profile. For certain applications, especially where increased strength and / or corrosion resistance is desired, yttrium may also be included.

[0033] 2. Terminology.

[0034] As used herein, "wire" or "wire product" includes continuous wire and wire products that can be continuously produced and wound onto spools for later distribution and use, such as wires with circular cross-sections and wires with non-circular cross-sections, including flat wires or strips. "Wire" or "wire products" also include other wire-based products, such as stranded wire, cables, coils, and tubing, which can be produced in specific lengths according to specific applications. In some exemplary embodiments, wire or wire products according to the present disclosure may have a diameter of up to 2.5 mm. In addition to wire and wire products, the principles of the present disclosure can be used to manufacture other material forms, such as rods with diameters greater than 2.5 mm to 20 mm. Thin sheets of material can also be made. Exemplary tubular structures can be in wire form or rod form with an inner diameter of 0.5 mm-4.0 mm and a wall thickness of 0.100 mm-1.00 mm. "Fine wire" refers to a wire with an outer diameter less than 1 mm.

[0035] As used herein, "fatigue strength" refers to the load level at which a material reaches or exceeds a given number of load cycles resulting in failure. In this article, the load level is given in the form of alternating strain, which is a standard for displacement or strain controlled fatigue testing, where the terminology is consistent with the terminology given in ASTM E606, the entire contents of which are incorporated herein by reference.

[0036] is a registered trademark of Fort Wayne Metals Research Products Corp. of Fort Wayne, IN, and refers to bimetallic or multimetallic composite wire products, including two or more concentric metal or alloy layers, usually with at least one outer layer disposed on a core wire, formed by drawing a tube or multiple tube layers over a solid metal wire core element.

[0037] "Impurities," "incidental impurities," and "trace impurities" are constituents of a material present in the material at less than 500 parts per million, or 0.05 weight percent, for any given element.

[0038] 3. Magnesium alloy

[0039] The magnesium-based alloy of the present invention may contain 1-5% by weight of lithium, 0.2-2.0% by weight of zinc, 0.1-0.5% by weight of calcium and 0.1-0.8% by weight of manganese, the remainder being magnesium and unavoidable impurities. For certain applications, yttrium may also be added in an amount of up to 2.5% by weight. All other elements are excluded from the alloy of the present invention, so that magnesium accounts for at least 89% by weight and at most 98.6% by weight of the total alloy.

[0040] These alloys have been found to provide a magnesium-based alloy that exhibits high ductility and high strength while using only elements that are native to the body or easily processed by the body. As described in further detail below, this combination of material properties provides an absorbable alloy with a predictable and suitable in vivo degradation profile, but it can also be efficiently produced in large quantities.

[0041] As further described below, the Mg-Li-Zn-Ca-Mn materials of the present invention exhibit high ductility. This ductility is beneficial to the manufacture and processing of their alloys because it allows for a greater amount of cold working, which can be reduced to a desired diameter with fewer cold drawing and annealing repetitions, and requires less energy to perform the cold working. The high ductility of the present materials also broadens the range of potential medical device applications by suppressing the likelihood of fracture, particularly in devices that require high levels of compressive strain, such as stents, staples, or ligature clips.

[0042] The Mg-Li-Zn-Ca-Mn materials of the present invention also exhibit relatively high strength, which can be increased to a desired level by cold working. This high strength also facilitates the use of the alloy in certain medical devices. For example, strength may be required for vessel wall support in stent applications or bone support in orthopedic or orthodontic device applications.

[0043] The alloys of the present invention also corrode predictably and favorably in in vivo environments.

[0044] Lithium is included to increase the ductility of the magnesium-based alloys of the present invention while also being easily and safely processed by the body. Lithium is a nutritional metal with a typical recommended daily dietary intake of 1 mg. Thus, relatively large amounts of lithium may be included as part of wire 730 or 731 or other materials made according to the present disclosure without adverse effects. At least 1.0 wt. % lithium is required to produce the desired increase in ductility, but lithium in excess of 5.0 wt. % results in a loss of strength, the potential for increased corrosion rates, and providing an unnecessarily high dose of lithium to the body.

[0045] Zinc is included as a contributor to solid solution strengthening of the alloy, and it can also form intermetallic compounds in the present material that act to mediate and control corrosion. In particular, when zinc is present in the required amount with calcium, and after certain heat treatments, zinc can contribute to the formation of Mg6ZmCa2 intermetallic compounds that are more expensive than base metals and can increase corrosion rates. Zinc is a nutritional metal that is easily and safely processed by the body, so relatively large amounts of zinc can be included as part of wire 730 or 731 or other materials made according to the present disclosure without adverse effects. At least 0.2 weight percent zinc is required to produce the desired strength increase, but zinc in excess of 2.0 weight percent will result in excessive Mg6ZmCa2 formation, which will result in corrosion rates that are too high for most applications.

[0046] Calcium is included as another contributor to solid solution strengthening of the alloy, which can also form intermetallic compounds in the material of the present invention, which are used to regulate and control corrosion. Mg2Ca is not as expensive as base metals and will reduce bulk corrosion by acting as a micro-current sacrificial anode. As previously mentioned, the Mg6ZmCa2 phase helps to increase bulk corrosion, so calcium can control the corrosion rate of magnesium alloys to a certain extent. Calcium is also a grain refiner that helps to improve the strength, ductility and machinability of the finished material. Like zinc, calcium is a nutritional metal that is easily and safely processed by the body, so relatively large amounts of calcium can be included as part of the wire 730 or 731 or other materials manufactured according to the present disclosure without adverse effects. At least 0.1 weight percent calcium is required to produce the desired strength increase, but calcium in excess of 0.5 weight percent will result in excessive Mg2Ca phases formed at the grain boundaries, which will reduce ductility and machinability.

[0047] Manganese is included as a further contributor to solid solution strengthening of the alloy. Manganese is able to reduce the deleterious effects of iron impurities in the material on the corrosion behavior of the alloy. Manganese is also a nutritional metal that is easily and safely processed by the body, so that relatively large amounts of manganese can be included as part of wire 730 or 731 or other materials made according to the present disclosure without adverse effects. At least 0.1 wt. % manganese is required to produce the desired increase in strength, but manganese in excess of 0.8 wt. % can result in excessive precipitation of α-Mn particles, which can negatively affect corrosion resistance.

[0048] Yttrium may also be optionally added to the Mg-Li-Zn-Ca-Mn alloy of the present invention. Yttrium is a rare earth element known to be well tolerated by the body. Yttrium (or its salts) has a relatively high solubility in water, which means that it is more easily processed by the body than some other rare earths. Adding yttrium can increase strength by solid solution strengthening and increase ductility by reducing texture and grain refinement. However, yttrium in excess of 2.5 wt. % results in reduced ductility and more Y-containing intermetallic compound particles, which can have a relatively long residence time in the body.

[0049] The above elements are an exhaustive list of materials for use in connection with the magnesium-based material of the present invention. As noted above, other elements are specifically excluded except for the presence of unavoidable impurities.

[0050] 4. Line structure containing Mg-Li-Zn-Ca-Mn-(Y)

[0051] In an exemplary embodiment, the Mg-Li-Zn-Ca-Mn material manufactured according to the present disclosure can be formed into thin medical grade wires 730, 731, such as Figure 1 The wires 730, 731 can then be formed or integrated into a medical device, for example braided into a device having an overall diameter Ds ( Figure 1 ) in the stent 700. The wires 730, 731 may each have a wire outer diameter Dw of less than, for example, 1 mm.

[0052] Alloys according to the present disclosure can first be formed into a bulk, such as by conventional casting methods. The bulk material is then formed into a suitable preformed material (e.g., a rod, plate, or hollow tube) by hot working the bulk material into the desired preformed size and shape. For the purposes of the present disclosure, hot working is achieved by heating the material to a high temperature above room temperature and performing the desired forming and shaping operations while the material is maintained at a high temperature. The resulting preformed material, such as a billet or a rod, is then further processed into an intermediate shape, such as a rod, wire, tube, sheet, or plate product, by repeated cold forming and annealing cycles. The method of forming the material may include pressing, extrusion, rolling, drawing, swaging, ECAP, ECAP-conform, high pressure torsion, severe plastic deformation, forging, pilgering, etc.

[0053] This intermediate material can be manufactured, for example, by a schedule of drawing and annealing to form an initial thick wire structure ready for final processing. Thereafter, wire 730 or 731 ( Figure 1-5 ) may be subjected to a final cold working conditioning step and possibly a final heat treatment step to impart the desired mechanical properties to the final wire product, as further described below.

[0054] exist Figure 2 In one exemplary embodiment shown, a single wire 731 made of Mg-Li-Zn-Ca-Mn material (including additional alloys thereof, as described herein) can first be produced using conventional methods, including a series of drawing and annealing to transform a preformed material (e.g., an ingot or rod) into a wire of a desired diameter before final processing. That is, the preformed material is passed through a die 736 ( Figure 2 ) to slightly reduce the outer diameter of the intermediate material while also lengthening the material, after which the material is annealed to release the internal stresses imparted to the material by the drawing process (i.e., retain cold work). The annealed material is then drawn through a new die 736 having a smaller final diameter to further reduce the diameter of the material and further lengthen the material. Further annealing and drawing of the material is repeated repeatedly until the material is formed into a wire structure ready for final processing into wire 731.

[0055] To form the composite line 730 ( Figure 3 ),For example The core 734 is inserted into the housing 732 to form an intermediate structure, which is then tapered at its ends to facilitate placement of the ends into the drawing die 736 ( Figure 3 ). The end protruding from the drawing die 736 is then clamped and stretched through the drawing die 736 to reduce the diameter of the structure and bring the inner surface of the shell 732 into firm physical contact with the outer surface of the core 734. More specifically, the initial drawing process reduces the inner diameter of the shell 732 so that the shell 732 fits over the outer diameter of the core 734 and the inner diameter of the shell 732 is equal to the outer diameter of the core 734, and when viewed in cross section, the inner core 734 completely fills the shell 732, as shown in FIG. Figure 3 shown.

[0056] An exemplary composite wire 730 may be formed using a Mg-Li-Zn-Ca-Mn alloy made in accordance with the present disclosure for shell 732 and another material for core 734. Exemplary materials for core 734 may include magnesium and magnesium alloys, zinc and zinc alloys, iron and iron alloys, non-absorbable alloys, or polymers.

[0057] The drawing step subjects the wire 730 or 731 to cold working. For the purposes of this disclosure, cold working methods affect material deformation at or near room temperature, such as 20-30° C. In the case of composite wire 730, drawing imparts cold work to both the material of the shell 732 and the core 734, with the cross-sectional area of ​​both materials being reduced simultaneously. The total cold work imparted to the wire 730 or 731 during the drawing step can be characterized by the following formula (I):

[0058]

[0059] Where "cw" is the cooling work defined by the reduction in initial material area, "D2s" is the outer cross-sectional diameter of the wire after one or more draws, and "D1s" is the outer cross-sectional diameter of the wire before the same one or more draws.

[0060] refer to Figure 2 and Figure 3 , the cold working step can be performed by the drawing process shown in the figure. As shown in the figure, the wire 730 or 731 is drawn through a lubricated die 736 having an output diameter D2s, which is smaller than the diameter D1s of the wire 730 or 731 before the drawing step. The outer diameter of the wire 730 or 731 is correspondingly reduced from the pre-drawing diameter D1s to the drawing diameter D2s, thereby imparting cold work cw.

[0061] Alternatively, net cold work may be accumulated in wire 730 or 731 by other processes such as cold forging, rolling the wire (e.g., into a flat strip or into other shapes), extrusion, bending, flow forming, severe plastic deformation, or pilgering. Cold work may also be imparted by any combination of techniques, including the techniques described herein, such as cold forging, followed by drawing through a lubricated die, and finally cold rolling into a wire form in the form of a strip or sheet or other shape. In one exemplary embodiment, the cold working step of reducing the diameter of wire 730 from D1s to D2s is performed in a single drawing, and in another embodiment, the cold working step of reducing the diameter of wire 730 from D1s to D2s is performed in multiple drawings, which are performed in sequence without any annealing steps in between. When the cold work cw is calculated using the above formula (I), it is assumed that no annealing is performed after the process of imparting cold work to the material.

[0062] For a process that repeats the drawing process of composite wire 730 without intermediate annealing, each subsequent drawing step further proportionally reduces the cross-section of wire 730 such that the ratio of the cross-sectional area of ​​shell 732 and core 734 to the total cross-sectional area of ​​wire 730 remains constant as the total cross-sectional area of ​​wire 730 decreases. Figure 3 , the ratio of the core outer diameter D1c before drawing to the shell outer diameter D1s before drawing is the same as the corresponding ratio after drawing. In other words, D1c / D1s=D2c / D2s.

[0063] Thermal stress relief, also referred to in the art as annealing, at a nominal temperature not exceeding the melting point of the wire material (or, for composite wires, the first or second material), is used to increase the ductility of the fully densified composite material between drawing steps, thereby allowing further plastic deformation by subsequent drawing steps. Further details regarding wire drawing are discussed in U.S. Patent No. 7,989,703, issued on August 2, 2011, entitled "Alternating Core Composite Wire," which is assigned to the assignee of the present invention, the entire disclosure of which is incorporated herein by reference.

[0064] Heating the wire 730 to a temperature sufficient to cause grain recrystallization removes the accumulated cold work. By fully annealing the material between draws, the cold work imparted by each repeated cold working process is released, thereby enabling the next repeated cold working process. In a full anneal, the cold worked material is heated to a temperature sufficient to fully release the stored internal stresses in the material, thereby releasing the stored cold work and "resetting" the cold work to zero.

[0065] On the other hand, the wire 730 or 731 subjected to drawing or other machining without a subsequent annealing process retains a certain amount of cold work. The amount of work retained depends on the total reduction in diameter from D1s to D2s and can be quantified based on the deformation of individual grains within the material caused by the imparted cold work. Figure 4 For example, wire 731 is shown in the annealed state, and the grains 12 are shown to be substantially equiaxed, that is, the grains 12 define a generally spherical shape, wherein the overall length G1 of the grains 12 is measured to be substantially the same regardless of the direction of measurement. After wire 731 is drawn (as described above), the equiaxed grains 12 are transformed into elongated grains 14 ( Figure 5 ), so that the grains 14 are longitudinal structures, defining an elongated grain length G2 (i.e., the longest dimension defined by the grains 14) and a grain width G3 (i.e., the shortest dimension defined by the grains 14). The elongation of the grains 14 is caused by the cold working process, and the longitudinal axis of the grains 14 is generally consistent with the drawing direction, such as Figure 5 shown.

[0066] The retained cold work of wire 731 after drawing can be expressed as the ratio of the elongated grain length G2 to the width G3, such that a larger ratio means that the grains have been "pulled" farther, and therefore means a greater amount of retained cold work. In contrast, annealing wire 731 after the intermediate drawing process recrystallizes the material, transforms the elongated grains 14 back to equiaxed grains 12 and "resets" the retained cold work ratio to 1:1 (i.e., no retained cold work).

[0067] For the Mg-Li-Zn-Ca-Mn material of the present invention, full annealing can be performed at a temperature of about 200-350°C for at least a few seconds (for thin wires (i.e., having a small cross-sectional area of ​​0.000127 square millimeters to 0.5 square millimeters)) to tens of minutes (for thicker materials (i.e., having a larger cross-sectional area of ​​1 square millimeter to 125 square millimeters)). Alternatively, full annealing can be performed at a higher temperature, such as 350-450°C, for a shorter time, such as a few milliseconds to less than 5 minutes, again depending on the cross-sectional area of ​​the material. Of course, a relatively high temperature annealing process can achieve full annealing with a relatively short time, while a relatively low temperature will generally achieve full annealing with a relatively long time. In addition, it can be expected that annealing parameters will vary with changes in wire diameter, with smaller diameters shortening the annealing time at a given temperature. Whether full annealing has been completed can be verified by a variety of means known in the art, such as microstructural inspection using a scanning electron microscope (SEM), mechanical testing of ductility, strength, elasticity, etc., and other methods. Furthermore, the effect of annealing parameters on the precipitation of Mg2Ca or Mg6ZmCa2 intermetallic phases can be considered when designing the manufacturing process for a specific device.

[0068] Further discussion of cold working and annealing methods may be found in U.S. Patent 8,840,735, issued September 23, 2014, entitled FATIGUE DAMAGE RESISTANT WIRE AND METHOD OF PRODUCTION THEREOF, the entire disclosure of which is incorporated herein by reference.

[0069] The resulting thick wire stock can then be ultimately processed into a final form, such as a thin wire suitable for integration into a stent or other medical device.Exemplary wire structures are described in more detail below.

[0070] 5. Line characteristics

[0071] As further described in detail in the following examples, the Mg-Li-Zn-Ca-Mn material of the present disclosure exhibits a combination of high strength and high ductility not found in other combinations of nutrient metals. When alloyed with yttrium, the Mg-Li-Y-Zn-Ca-Mn material of the present disclosure also outperforms other combinations of nutrient metals plus yttrium.

[0072] Although elongation at rupture is used to represent the ductility of the wires 730, 731 discussed herein, the elongation at rupture of a material is not necessarily indicative of the functional ductility of the material. A material having a relatively low elongation at rupture may have a relatively high ductility when ductility is considered to be the ability to withstand high bending strains or significant cold reduction (e.g., by drawing) without rupture.

[0073] Mg-Li-Zn-Ca-Mn made in accordance with the present disclosure and without stored cold work exhibits ductility sufficient to allow at least 10%, 15%, 20% or 25% elongation before rupture, with high ductility being associated with lithium levels at the upper end of the range 1.0-5.0 weight %, and vice versa. This high ductility allows the material to be adequately cold worked, either as a processing step (followed by annealing) or to strengthen the material for final structure. The cold working capability of the Mg-Li-Zn-Ca-Mn material of the present invention can be as high as, for example, 60%, 75% or 90%, where the cold working capability corresponds to the ductility. The addition of yttrium can improve ductility, particularly in material that has just been annealed (i.e., without retained cold work), because the grain size is refined and the crystal texture is reduced.

[0074] Mg-Li-Zn-Ca-Mn made according to the present disclosure and without stored cold work also exhibits high strength, with the potential to achieve higher strength through cold working treatment. In the as-annealed state, the ultimate strength of the Mg-Li-Zn-Ca-Mn material of the present invention is at least 25 ksi, 32 ksi or 40 ksi, and higher strength is associated with zinc, calcium and manganese at the upper limits of their respective ranges of 0.2-2.0 wt%, 0.1-0.5 wt% and 0.1-0.8 wt%, and vice versa. For example, Fig. 6A The stress-strain curve of a Mg-2Li-1.2Zn-0.4Ca-0.4Mn alloy made according to the present disclosure is shown, as further described in the Examples below. Fig. 6A The alloys of the present invention exhibit increased yield strength and ultimate strength compared to the binary Mg-4Li alloy also shown in . Figure 6B The additional properties of the same Mg-2Li-1.2Zn-0.4Ca-0.4Mn alloy before and after cold working, as well as the properties of the Mg-2Li-2Y-1.2Zn-0.4Mn-0.4Ca alloy before and after cold working are illustrated. Fig. 6A and 6B The nominal strength values ​​of any of the Mg-Li-Zn-Ca-Mn alloys of the present invention may be increased by 25%, 50% or 100% by cold working, with the greater cold working potential corresponding to the ductility of the above materials.

[0075] Similarly, the Mg-Li-Zn-Ca-Mn materials of the present invention exhibit yield strengths of at least 20 ksi, 25 ksi or 30 ksi, with similar corresponding relationships to the levels of zinc, calcium and manganese and similar strength increases achieved with the addition of yttrium.

[0076] Steering Figure 6CThe Mg-Li-Zn-Ca-Mn material of the present invention also exhibits a high in vivo life and a predictable long degradation curve. Its failure time when subjected to load in a corrosive environment (as described in detail in Example 4 below) far exceeds that of known binary Mg-Li alloys, such as Figure 6C 4Li, and is generally comparable to Mg-Zn-Ca-Mn alloys, which lack the advantages of lithium discussed herein. Although the failure time of the present Mg-Li-Zn-Ca-Mn material is slightly lower than that of WE43, it may be sufficient for many applications while also providing an improved in vivo biocompatibility profile compared to WE43.

[0077] Within the alloy composition ranges of the present invention discussed herein, the time to failure of a 0.010 inch diameter wire in the as-annealed condition can be expected to exhibit an average life of at least 30 hours in a Hanks' Balanced Salt Solution maintained at 37°C and 7.4 pH, while also maintained at an initial stress of 110 MPa. Similarly, the time to failure of a 0.010 inch diameter wire in a cold worked condition with 50% retained cold work can be expected to exhibit an average life of at least 30 hours in a Hanks' Balanced Salt Solution maintained at 37°C and 7.4 pH, while also maintained at an initial stress of 110 MPa. In addition, any wire made according to the present disclosure and suitable for use in vivo can be expected to exhibit an average life of at least 24 hours under typical in vivo conditions (i.e., at body temperature, positioned in the body, and subjected to typical stresses associated with the medical devices described herein).

[0078] 6. Medical device applications

[0079] A variety of medical devices can be made from the materials of the present invention, which are beneficial for any device whose presence and function in the body may change and weaken over time. Some exemplary such devices are described below, and it should be understood that the materials of the present invention can also be used in any other suitable medical device applications.

[0080] As described above, wires 730, 731 may be used in vascular devices such as stent 700 ( Figure 1 ) or 700A( Figure 1A ). Stent 700 can provide a high degree of initial vascular support, and this vascular support can then slowly decrease over time in vivo as wires 730, 731 degrade. Other wire-based vascular devices suitable for use with wires 730, 731 include aneurysm occlusion devices, septal occluders such as occluder 900 ( Figure 8 ), shunts, filters, and grafts.

[0081] Wires 730, 731 or other structures may also be used for orthopedic fixation. Exemplary applications include screws such as screw 800 ( Figure 7 ), pins, nails, Kirchner wires (K-wires), and cerclage cables (e.g., for sternal closure), all of which can be implanted at the surgical site to provide high levels of mechanical support to adjacent tissues and then degrade over time as the tissue itself heals.

[0082] Other medical device applications of wires 730, 731 include surgical interventional devices such as surgical staples, ligature clips, and tacks. These devices can be used to achieve temporary closure of some relevant portion of the anatomical structure and then release the closure over time as the device degrades. Still other applications may include devices for renal treatment, temporary pacing leads, and many other indications.

[0083] Example

[0084] The following non-limiting examples illustrate various features and characteristics of the present invention but should not be construed as limiting thereof.

[0085] In these examples, exemplary Mg-Li-Zn-Ca-Mn and Mg-Li-Y-Zn-Ca-Mn single alloy wires according to the present disclosure were produced, tested and characterized, particularly with respect to the processability and mechanical strength of the material.

[0086] The following examples demonstrate that the MgLiZnMnCa alloy of the present invention has an optimal combination of strength, ductility, corrosion resistance and biocompatibility for absorbable suture applications requiring high ductility, such as staples, ligatures and stents.

[0087] The mechanical properties of each wire sample were evaluated by uniaxial tensile testing on an Instron Model 5565 testing machine available from Instron of Norwood, Massachusetts, USA. More specifically, burst uniaxial tensile testing of the wire material was used to quantify the ultimate strength, yield strength, axial stiffness, and ductility of the candidate material using Structure- Property Relationships in Conventional and Nanocrystalline NiTi Intermetallic Alloy Wire, Journal of Materials Engineering and Performance 18, 582-587 (2009) by Jeremy E. Schaffer, the entire disclosure of which is hereby expressly incorporated herein by reference. These tests were run using a servo-controlled Instron load frame according to industry standards for tensile testing of metallic materials.

[0088] For rotating beam fatigue testing according to embodiments herein, a wire sample is cut to a length of approximately about 118 mm (e.g., for a 0.33 mm diameter wire) and then secured to a rotatable jaw at its axial ends. The free portion of the wire between the jaws is bent to introduce the desired tensile strain at the "peak" or outermost portion of the bend. Directly opposite this bend peak, the wire is subjected to a compressive strain equal to the tensile strain, the nominal values ​​of tensile and compressive strains being referred to herein as "strain amplitudes." The jaws are then rotated in unison (i.e., each jaw rotates at the same speed and in the same direction) so that the region of maximum tensile strain rotates about the wire "peak" and transitions to the region of maximum compressive strain, with the jaws and wire each rotating 180 degrees. Rotating beam fatigue testing is further described in ASTM E2948-14, the entire disclosure of which is hereby expressly incorporated herein by reference.

[0089] Example 1

[0090] The Mg-Li-Zn-Mn-Ca alloy of the present disclosure is produced to have 2 wt% Li, 1.2 wt% Zn, 0.4 wt% Mn and 0.4 wt% Ca, with the balance being magnesium and unavoidable impurities. This alloy is first made into an ingot by vacuum induction melting the respective material components, and then the material is cast into a 2-inch mold.

[0091] The ingot was then hot worked by extrusion at a temperature of 325°C using a ram speed of 10 inches / minute to a 0.5 inch diameter. The extruded rod was then centerlessly ground and processed by a standard wire drawing operation through a series of cold draws to a single round wire, as described above, with a final diameter of 0.0079 inches.

[0092] The wire was then fully annealed as described above to produce a first final wire structure, which was subjected to uniaxial tensile testing as described above. The wire exhibited an ultimate tensile strength of 37 ksi and a yield strength of 30 ksi. The wire was able to elongate 14% before failure. These results are shown in Table 1. Figure 6B This is shown as line "A" in the figure, which is the dashed line below.

[0093] Another sample of the single wire was further cold drawn to a final diameter of 0.005 inches and was not annealed, resulting in a second final wire structure with 75% retained cold work. This wire was subjected to the same uniaxial tensile tests as the first final wire structure and exhibited an ultimate tensile strength of 64 ksi and a yield strength of 56 ksi. The wire was able to elongate 7% before failure. These results are shown in Figure 6B This is shown as line "B" which is the solid line above.

[0094] Example 2

[0095] The Mg-Li-Y-Zn-Mn-Ca alloy of the present disclosure is produced to have 2 wt% Li, 2 wt% Y, 1.2 wt% Zn, 0.4 wt% Mn and 0.4 wt% Ca, with the balance being magnesium and unavoidable impurities. Thus, the alloy has the same chemistry as the alloy in Example 1 above, but also contains 2 wt% yttrium. This alloy is first made into an ingot by vacuum induction melting the various material components, and then the material is cast into a 2-inch mold.

[0096] The ingot was then hot worked by extrusion at a temperature of 325°C using a ram speed of 10 inches / minute to a 0.5 inch diameter. The extruded rod was then processed by a standard wire drawing operation through a series of cold draws and anneals to a single round wire, as described above, with a final diameter of 0.0099 inches.

[0097] The Mg-Li-Y-Zn-Mn-Ca material of this example demonstrates reduced ductility and machinability, requiring additional annealing to achieve a given diameter reduction compared to the Mg-Li-Zn-Mn-Ca material of Example 1. However, it requires less annealing for a given diameter reduction compared to other magnesium alloys such as WE43 or Mg-Zn-Ca.

[0098] The wire was then fully annealed as described above to produce a first final wire structure, which was subjected to uniaxial tensile testing as described above. The wire exhibited an ultimate tensile strength of 39 ksi and a yield strength of 33 ksi. The wire was able to elongate 19% before failure. These results are shown in Table 1. Figure 6B , which is the upper dashed line. Thus, compared to the annealed Mg-Li-Zn-Mn-Ca material described in Example 1 above, it can be seen that the addition of yttrium improves the strength and ductility in the annealed state (i.e., no cold work retained).

[0099] Another sample of the single wire was further cold drawn to a final diameter of 0.005 inches and was not annealed, resulting in a second final wire structure with 75% retained cold work. This wire was subjected to the same uniaxial tensile test as the first final wire structure and exhibited an ultimate tensile strength of 61 ksi and a yield strength of 45 ksi. The wire was able to elongate 9% before failure. These results are shown in Figure 6B , which is the solid line below. Thus, compared to the cold worked Mg-Li-Zn-Mn-Ca material described in Example 1 above, it can be seen that the addition of yttrium does not increase strength but does increase ductility.

[0100] Example 3

[0101] A conventional Mg-Li alloy having 4 wt% Li, the balance being magnesium and inevitable impurities, was produced. This alloy was first manufactured into an ingot by vacuum induction melting the respective material components, and then the material was cast into a 2-inch mold.

[0102] The ingot was then hot worked by extrusion at a temperature of 300°C using a ram speed of 10 inches / minute to a 0.5 inch diameter. The extruded rod was then processed by a standard wire drawing operation through a series of cold draws and anneals to a single round wire, as described above, with a final diameter of 0.0079 inches.

[0103] like Fig. 6A As shown by the dashed line in , the conventional Mg-Li material of this example demonstrates equivalent or increased ductility and machinability compared to the material of Example 1, requiring equivalent or less annealing to achieve a given diameter reduction. However, the strength of this alloy is very low compared to the material described in Example 1, as shown in FIG. Fig. 6A and Figure 6B shown.

[0104] The wire was then fully annealed as described above to produce a first final wire structure, which was subjected to uniaxial tensile testing as described above. The wire exhibited an ultimate tensile strength of 28 ksi and a yield strength of 17 ksi. The wire was able to elongate 16% before failure.

[0105] Thus, compared to the annealed Mg-Li-Zn-Mn-Ca material described in Example 1 above or the Mg-Li-Y-Zn-Mn-Ca material described in Example 2, it can be seen that the addition of Zn, Mn, Ca, and optionally Y can produce an increase in annealed yield strength of 76%-94% while maintaining good ductility.

[0106] Example 4

[0107] In order to evaluate the corrosion behavior of the alloys of the present invention compared to other known alloys, the following experiments were conducted. Wires having a final diameter of 0.010 inches were made from the following four different alloys:

[0108] -Mg-2Li-1.2Zn-0.4Mn-0.4Ca, according to the present disclosure and also discussed in Examples 1 and 2 above;

[0109] -Mg-1Zn-0.3Ca-0.1Mn, as a control sample of a similar nutrient metal alloy without lithium;

[0110] - Conventional WE43, as a control sample of rare earth-containing alloy; and

[0111] - Conventional Mg-4Li, as a control sample, also discussed in Example 3 above.

[0112] Each of the four wires was produced as an annealed wire (i.e., no cold work retained) and a cold worked wire (i.e., 45-75% cold work retained), for a total of eight separate alloy / condition combinations. At least two samples of each alloy / condition combination were tested as described below. For the cold worked wires, the WE43 wire had 75% retained cold work, the Mg-1Zn-0.3Ca-0.1Mn had 50% retained cold work, the Mg-2Li-1.2Zn-0.4Mn-0.4Ca had 50% retained cold work, and the MgLi had 45% retained cold work. These cold working levels are intended to achieve the mechanical properties of each wire typically required for medical device applications.

[0113] Each wire sample was subjected to corrosion in Hanks' Balanced Salt Solution (HBSS) maintained at 37°C and 7.4 pH, while also being maintained at an initial stress of 16 ksi (110 MPa) by deadweight. HBSS is a physiologically relevant inorganic salt solution that is considered to be an adequate magnesium corrosion medium in in vitro testing. HBSS is commercially available and can be purchased from Millipore Sigma (formerly Sigma Aldrich) in St. Louis, Missouri, USA. For this example, the commercially available HBSS was modified with 1.6 g / L sodium bicarbonate and 0.265 g / L calcium chloride, which are also commercially available and can be purchased from Sigma Aldrich.

[0114] The time to wire rupture was measured for each sample, providing a measure of relative corrosion resistance.

[0115] The experimental results are as follows Figure 6CAs shown. The average life of the MgLiZnMnCa alloy of the present invention in the cold worked form is at least 40 hours and in the annealed form is at least 33 hours. As expected, this failure time is less than the rare earth-containing WE43, which has an average life of more than 50 hours in both cold worked and annealed forms. However, the life of the MgLiZnMnCa alloy is significantly longer than that of the Mg4Li binary alloy, which fails after about 20 hours and 11 hours in cold worked and annealed forms, respectively. This shows that the in vivo life of the present alloy is much longer than that of the baseline binary alloy.

[0116] When comparing the MgLiZnMnCa alloy of the present invention to a conventional MgZnCaMn alloy, the life under cold working conditions is only slightly reduced by the addition of Li, from about 45 hours for the MgZnCaMn alloy to the aforementioned time of about 40 hours for the MgLiZnMnCa alloy of the present invention. Surprisingly, the life of the MgLiZnMnCa alloy under annealing conditions (about 33 hours) is longer than that of the MgZnCaMn alloy (about 28 hours), which is unexpected because the reactivity of Li is greater. Therefore, the MgLiZnMnCa alloy of the present invention exhibits better or comparable in vivo life than similar biocompatible alloys, while also exhibiting excellent strength and ductility.

[0117] Although the present invention has been described as having an exemplary design, the present invention may be further modified within the spirit and scope of the present disclosure. Therefore, this application is intended to cover any variation, use or adaptation of the present invention using its general principles. In addition, this application is intended to cover deviations from the present disclosure that are within the known or customary practices in the field to which the present invention belongs and fall within the limits of the appended claims.

Claims

1. An alloy for an absorbable medical device, the alloy comprising: 1.0-5.0 wt% lithium; 0.2-2.0 wt. % zinc; 0.1-0.5% by weight of calcium; 0.1-0.8 wt. % manganese; and The balance is magnesium and unavoidable impurities.

2. The alloy of claim 1 wherein the alloy retains no cold work and exhibits an ultimate tensile strength of up to 34 ksi.

3. The alloy of claim 1 wherein the alloy has a retained cold work of 75% and exhibits an ultimate tensile strength of up to 64 ksi.

4. The alloy of claim 1 wherein the alloy retains no cold work and exhibits a yield strength up to 26 ksi.

5. The alloy of claim 1 wherein the alloy has a retained cold work of 75% and exhibits a yield strength of up to 56 ksi.

6. The alloy of claim 1 wherein the alloy retains no cold work and exhibits ductility sufficient to allow 14% elongation before rupture.

7. The alloy of claim 1 wherein the alloy has 75% retained cold work and exhibits ductility sufficient to allow 7% elongation before rupture.

8. The alloy of claim 1 wherein gold retains no cold work and exhibits an average lifetime of at least 30 hours in a Hank's balanced salt solution maintained at 37°C and 7.4 pH while also being maintained at an initial stress of 110 MPa.

9. The alloy of claim 1, wherein the alloy has a retained cold work of at least 50% and exhibits an average life of at least 30 hours in a Hank's balanced salt solution maintained at 37°C and 7.4 pH while also being maintained at an initial stress of 110 MPa.

10. The alloy of claim 1, wherein the alloy retains no cold work and exhibits: Achieves an ultimate tensile strength of 34ksi; Achieves a yield strength of 26ksi; Ductility sufficient to allow 14% elongation before rupture; and The average lifetime was at least 30 hours in Hank's balanced salt solution maintained at 37°C and 7.4 pH while also being maintained under an initial stress of 110 MPa.

11. The alloy of claim 1 , wherein the alloy has a retained cold work of at least 50% and exhibits: Achieves an ultimate tensile strength of 64ksi; Achieves a yield strength of 56 ksi; Ductility sufficient to allow 7% elongation before rupture; and The average lifetime was at least 30 hours in Hank's balanced salt solution maintained at 37°C and 7.4 pH while also being maintained under an initial stress of 110 MPa.

12. The alloy of claim 1 further comprising yttrium in an amount up to 2.5 wt. %.

13. The alloy of claim 12, wherein the alloy retains no cold work and exhibits an ultimate tensile strength of up to 39 ksi.

14. The alloy of claim 12, wherein the alloy has a retained cold work of 75% and exhibits an ultimate tensile strength of up to 61 ksi.

15. The alloy of claim 12, wherein the alloy retains no cold work and exhibits a yield strength up to 33 ksi.

16. The alloy of claim 12, wherein the alloy has a retained cold work of 75% and exhibits a yield strength of up to 45 ksi.

17. The alloy of claim 12 wherein the alloy retains no cold work and exhibits ductility sufficient to allow 19% elongation before rupture.

18. The alloy of claim 12, wherein the alloy has a retained cold work of 75% and exhibits ductility sufficient to allow a 10% elongation before rupture.

19. A wire formed from the alloy of any one of claims 1 to 18.

20. A medical device formed from the alloy of any one of claims 1-18.

21. The medical device of claim 20, wherein the medical device is a vascular device.

22. The medical device of claim 20, wherein the medical device is an orthopedic fixation device.

23. The medical device of claim 20, wherein the medical device is an interventional surgical device.

Citation Information

Patent Citations

  • Alternating core composite wire

    US7989703B2

  • Fatigue damage resistant wire and method of production thereof

    US8840735B2

  • Biodegradable wire for medical devices

    US20160138148A1